Penerapan Multimedia Pembelajaran Berbasis Kecerdasan Buatan (AI) di Madrasah Ibtidaiyah Swasta (MIS) Musawiyah - Rusdi, Muhammad; Suherman; Yani, Achmad; Suprianto; Pinem, Mhd Daud (Politeknik Negeri Medan, 2025)
The Community Partnership Program (PKM) collaborated with Madrasah Ibtidaiyah Swasta (MIS) Musawiyah, located in Dusun Kebun Kacang, Padang Tualang District, Langkat Regency, North Sumatra Province. The general objective of the Community Partnership Program (PKM) implementation is to help solve partner problems in improving the quality of learning through the application of learning technology based on Artificial Intelligence (AI). The specific objective is to provide training for MIS Musawiyah teachers on implementing AI-based multimedia learning, as well as to provide one unit of LCD projector as supporting equipment in the teaching and learning process at the madrasah. The methods used in this PKM program consist of several stages. The initial stage started with collecting data through surveys and interviews with the Head of Madrasah to identify the partner’s needs and problems. Based on these results, an engagement program was designed to cover implementation and evaluation activities over three months. The results show a significant increase in teacher competence, from 20% before training to 90% after training, as well as the creation of a more innovative and participatory learning culture. This activity was considered successful in improving teachers’ digital competence by an average of 70–80% and enhancing learning facilities, thereby creating a more attractive and effective learning environment. Evaluation demonstrates that the application of AI-based multimedia increased teacher creativity, learning effectiveness, and student participation.